2013
DOI: 10.1590/s1679-78252013000500009
|View full text |Cite
|
Sign up to set email alerts
|

Stick-slip analysis in vibrating two-layer beams with frictional interface

Abstract: This paper attempts to present a new analysis for dynamical behavior of two-layer beams with frictional interface which held together in a pressurized environment, including stick-slip nonlinear phenomenon. To achieve a proper outlook of two-layer beam structures behavior, it is essential to realize the mechanisms of motion precisely. Coupled equation of transversal and longitudinal vibration of two-layers in the presence of dry friction is derived and nondimensionalized. Furthermore, free and forced vibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In the last decades, the stress distribution, bearing capacity et al mechanical properties of laminated beams has been extensive researched (Gao and Wu, 2007;Sun, 2004;Li, 2002;Liu et al, 2021;Sedighi et al, 2013;Huang, 2015;Li and Liu, 2021). Based on the free-laminated beams, the calculation method of bending moment when each layer beam is compacted was proposed by Jie (Jie, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, the stress distribution, bearing capacity et al mechanical properties of laminated beams has been extensive researched (Gao and Wu, 2007;Sun, 2004;Li, 2002;Liu et al, 2021;Sedighi et al, 2013;Huang, 2015;Li and Liu, 2021). Based on the free-laminated beams, the calculation method of bending moment when each layer beam is compacted was proposed by Jie (Jie, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chen and Deng [7] found that a FE model was able to replicate the slip damping observed in the classical models of Goodman and Klumpp [1] and of Metherell and Diller [8]. FEs have also been used to study the frictional damping behaviour of unbonded multi-layer beams [9,10]. This has included a direct comparison of the hysteresis behaviour obtained both numerically and by physical experiment which showed that the static spring rate gave good agreement [11].…”
Section: Introductionmentioning
confidence: 99%